If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5A + 10 = 5 Reorder the terms: 10 + -5A = 5 Solving 10 + -5A = 5 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -5A = 5 + -10 Combine like terms: 10 + -10 = 0 0 + -5A = 5 + -10 -5A = 5 + -10 Combine like terms: 5 + -10 = -5 -5A = -5 Divide each side by '-5'. A = 1 Simplifying A = 1
| -2A+1=4 | | 3a+1=2x+4 | | 4=2x-10 | | y=(x-3)(x-3)+(x-9)(x-9) | | 3/4x=7/1 | | 6.5/500= | | -3+A=2 | | 6(7d-12)=30 | | 4n=6.58 | | 28y+4=0 | | z/8-5=5 | | 6-3(x+10)=-5 | | ln(e)=0.3ln(x) | | (X^2-4)(x^2-4)=127449 | | 8x-7=59 | | -A-1=-3 | | 8*m*n*7*m*m*n= | | y=(x+1)(x+3)(x-4) | | (x)(x)+14x=0 | | 3(8+6y)=2(9y-12) | | 8mn*7m*7mn= | | Xsquared+14x+c=0 | | 3x+X=7 | | 4(3x+7)=2(6x+14) | | 7xw*2w= | | -5A=-15 | | 5x+7/2=3x+5/4+2x+3 | | 14+6b+7-2b= | | 6(3x-4)=60 | | 2(y+4)=7(y-1) | | 1-X+X=11 | | 43/6/2 |